2009
DOI: 10.1021/nn900451a
|View full text |Cite
|
Sign up to set email alerts
|

Layer-by-Layer-Coated Gelatin Nanoparticles as a Vehicle for Delivery of Natural Polyphenols

Abstract: Natural polyphenols with previously demonstrated anticancer potential, epigallocatechin gallate (EGCG), tannic acid, curcumin, and theaflavin, were encased into gelatin-based 200 nm nanoparticles consisting of a soft gel-like interior with or without a surrounding LbL shell of polyelectrolytes (polystyrene sulfonate/polyallylamine hydrochloride, polyglutamic acid/poly-l-lysine, dextran sulfate/protamine sulfate, carboxymethyl cellulose/gelatin, type A) assembled using the layer-by-layer technique. The characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
261
0
4

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 398 publications
(269 citation statements)
references
References 42 publications
4
261
0
4
Order By: Relevance
“…Shutava et al utilized a polyelectrolyte layer-by-layer technique to coat EGCG over gelatin core nanoparticles. It was shown that the biological activity of EGCG, blocking the signaling pathway of the breast cancer cell line in their study, remained [42]. Therefore, the utilization of biopolymers to protect EGCG from oxidation is an essential practice for forming a drug delivery system.…”
Section: Instability Of Free-egcg In Solutionsmentioning
confidence: 99%
“…Shutava et al utilized a polyelectrolyte layer-by-layer technique to coat EGCG over gelatin core nanoparticles. It was shown that the biological activity of EGCG, blocking the signaling pathway of the breast cancer cell line in their study, remained [42]. Therefore, the utilization of biopolymers to protect EGCG from oxidation is an essential practice for forming a drug delivery system.…”
Section: Instability Of Free-egcg In Solutionsmentioning
confidence: 99%
“…There have been a number of recent reviews focusing on the encapsulation of the more widely used polyphenols, discussing their effectiveness, variations, developments and trends (Barras et al, 2009;Das, Ng, 2010;Di Mattia et al, 2009;Dube et al, 2010;Ersus, Yurdagel, 2007;Fang et al, 2006;Hu et al, 2008;Kosaraju, Dath, Lawrence, 2006;Laine et al, 2008;Liang et al, 2011;Lucas-Abellan et al, 2007;Mourtzinos et al, 2007;Shi et al, 2007;Shutava et al, 2009;Tommasini et al, 2005;Zhang, Mou, Du, 2007;Xiong et al, 2006;Yu, Huang, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand both the nanoparticles with and without EGCG did not inhibit HGF-induced signalling after pre-incubation of 30 min. However, at the 5 h time-point the gelatin coated nanoparticle containing EGCG blocked HGF-induced signalling, therefore demonstrating that EGCG activity was retained but released slowly (Shutava et al, 2009). Recently, curcumin nanoparticles have shown enhanced bioavailability and greater cytotoxicity against breast cancer cells.…”
Section: Novel Drug Delivery Of Natural Compoundsmentioning
confidence: 97%